Popular representations of development insights from novels, films, television and social media (London Routledge, 2014)
"Although the academic study of development is well established, as is also its policy implementation, less considered are the broader, more popular understandings of development that often shape agendas and priorities, particularly in representative democracies. Through its accessible and provocative chapters, Popular Representations of Development introduces the idea that while the issue of "development" -- defined broadly as problems of poverty and social deprivation, and the various agencies and processes seeking to address these -- is normally one that is discussed by social scientists and policy makers, it also has a wide "popular" dimension. Development is something that can be understood through studying literature, films, and other non-conventional forms of representation. It is also a public issue, one that has ironically been associated with musical movements such as Live Aid and increasingly features in newer media such as blogs and social networking. The book connects the effort to build a more holistic understanding of development issues with an exploration of the diverse public sphere in which popular engagement with development takes place. This book gives students of development studies, media studies and geography as well as students of humanities engaging with global development issues a variety of perspectives from different disciplines to open up this new field for discussion
Includes bibliographical references and index.
Keywords: BUSINESS & ECONOMICS / Development / Economic Development